Race and education, 1954-2007 - Wolters, Raymond, 1938- (University of Missouri Press, 2008)
"Retracing Supreme Court decisions on race and education beginning with the Brown v. Board of Education decision, Wolters distinguishes between desegregation and integration and shows how devastating educational and cultural consequences resulted from subsequent Supreme Court decisions that conflated the two and led to racial balancing policies that have backfired"--Provided by publisher.